A Stress‐Free and Textured GaP Template on Silicon for Solar Water Splitting. (28th May 2018) - Lucci, Ida; Charbonnier, Simon; Vallet, Maxime; Turban, Pascal; Léger, Yoan; Rohel, Tony; Bertru, Nicolas; Létoublon, Antoine; Rodriguez, Jean‐Baptiste; Cerutti, Laurent; Tournié, Eric; Ponchet, Anne; et al.
Abstract: This work shows that a large‐scale textured GaP template monolithically integrated on Si can be developed by using surface energy engineering, for water‐splitting applications. The stability of (114)A facets is first shown, based on scanning tunneling microscopy images, transmission electron microscopy, and atomic force microscopy. These observations are then discussed in terms of thermodynamics through density functional theory calculations. A stress‐free nanopatterned surface is obtained by molecular beam epitaxy, composed of a regular array of GaP (114)A facets over a 2 in. vicinal Si substrate. The advantages of such textured (114)A GaP/Si template in terms of surface gain, band lineups, and ohmic contacts for water‐splitting applications are finally discussed. Abstract : A large‐scale stress‐free textured GaP template monolithically integrated on Si is produced by surface energy engineering for water‐splitting applications. The stability of GaP{114} facets is examined thermodynamically. The benefits of using a textured (114)A GaP/Si template for water‐splitting applications, in terms of surface gain, band lineups, and ohmic contacts are discussed.